TREATMENT OPTIMIZATION IN PATIENTS WITH STABLE ANGINA PECTORIS: FOCUS ON VERAPAMIL SR - I. M. Sokolov (Рациональная фармакотерапия в кардиологии)
Possibilities of angina pectoris pharmacotherapy are analyzed. Achievement of target heart rate (HR) 55-60 beats per minute in these patients is possible due to three classes of antianginal medications that slow down HR: beta blockers (BB), If-channel inhibitors, nondihydropyridine calcium channel blockers (CCB). Nondihydropyridine CCB verapamil in slow release (SR) formulation is focused. The main results of randomized clinical trials (APSIS, VHAS, CRIS, EVERESTH, VAMPHYRE, INVEST, VESPA, DAVIT-1, DAVIT-2), which have proven efficacy and safety, are presented. Verapamil SR is indicated for the treatment of angina pectoris in patients without history of myocardial infarction (MI); angina patients experienced MI without systolic heart failure and with contraindications to BB; angina with arterial hypertension; left ventricular diastolic dysfunction; peripheral arteries obliterating atherosclerosis; silent myocardial ischemia; vasospastic angina; angina associated with supraventricular cardiac arrhythmias (especially in permanent atrial fibrillation) except Wolff-Parkinson-White and Lown-Ganong-Levine syndromes; after coronary angioplasty and the placement of bare metal stents.